2014
DOI: 10.1371/journal.pone.0105854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Etiology and Outcomes of Community-Acquired Pneumonia in Patients with Chronic Obstructive Pulmonary Disease

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is a frequent complication of chronic obstructive pulmonary disease (COPD), but previous studies are often contradictory.ObjectivesWe aimed to ascertain the characteristics and outcomes of CAP in patients with COPD as well as to determine the risk factors for mortality and Pseudomonas aeruginosa pneumonia in COPD patients with CAP. We also describe the etiology and outcomes of CAP in COPD patients receiving chronic oxygen therapy at home and those receiving inhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 39 publications
8
48
0
4
Order By: Relevance
“…In addition, that meta-analysis focused exclusively on mortality, the other clinically important outcomes including length of hospital stay, ICU admission and need for mechanical ventilation were not investigated. Furthermore, several studies 16,19,27 with conflicting results have recently been published. In contrast to the previous metaanalysis, our meta-analysis provides evidence that co-morbid COPD is not associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, that meta-analysis focused exclusively on mortality, the other clinically important outcomes including length of hospital stay, ICU admission and need for mechanical ventilation were not investigated. Furthermore, several studies 16,19,27 with conflicting results have recently been published. In contrast to the previous metaanalysis, our meta-analysis provides evidence that co-morbid COPD is not associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…All cohort studies ascertained the diagnosis of CAP based on chest radiographic findings, whereas the two case-control studies identified the cases of CAP according to the International Classification of Diseases (ICD-10) codes. Eight cohort studies confirmed the presence of COPD by spirometric criteria, 15,[18][19][20]23,[26][27][28] whereas the case-control studies 16,29 and one cohort study 17 identified COPD patients through medical records. The main characteristics of the included studies are summarized in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations